Effect of Fermenter Configuration, Antifoam and Agitation Speed on the Performance of Kojic Acid Fermentation by Aspergillus flavus Link Strain 44-1 - Kamarudin, Suryani (2002)
The effect o f agitation speed on growth morphology and cell breakage of Aspergillus flavus Link strain 44-1 and its relationship to kojic acid production was carried out using 2 L stirred tank fermenter. From the shake flask experiments, it was found that the addition of silicone based antifoam, even at very low concentration (0.001% v/v), reduced growth and kojic acid production significantly. In order to find the suitable approach for minimizing foam formation during kojic acid fermentation in stirred tank fermenter, the effect of several fermenter configuration based on number of impeller and barnes used on foam formation have been tested. The degree of foaming was greatly influenced by the fermenter configuration. The fermenter with 4-barnes and a single Rushton turbine was found suitable to avoid excessive foaming during the fermentation.Two mechanisms of cell damage, (i) breaking up, and (ii) shaving off were noticed at agitation speed of 600 and 800 rpm. The breaking up results in the formation of ne w pellet and fragments while the shaving off results in the fomlation of shaved pellet and free filamentous mycelia. Agitation speed also greatly influenced the growth morphology of Aspergillus flavus, in which, at low speed the pellets were weak and fluffy while at high speed the more stable pellets were formed. The agitation speed 600 rpm was found optimal for growth (13.11 g/l) of Aspergillus flavus and kojic acid production (32.95 g/l), which was associated to growth in the form of pellet with an average size of 1.32 mm. This gave the yield and overall productivity of 0.331 g/g and 2.059 g/L.day, respectively. The models based on logistic and Luedeking- Piret equations were found suitable to describe kojic acid fermentation by Aspergillus jlavus Link strain 44-1 at certain fermentation conditions. Kojic acid production was found nongrowth associated process and the kinetic parameters values obtained from modelling can be used to verify the fermentation data. The Aspergillus jlavus culture during kojic acid fermentation was found to be a non-Newtonian Pseudoplastic type with flow behavior index less than one. The flow was in transitional region with Reynolds number between 0 and 10⁴ The power consumption in this experiment was proportional to the agitation speed applied by the impeller and ranged between 0.3 to 7.0 J/s.